Young Turkish Tourists’ Religious Tourism Motivations, Perceptions and Intentions About a Religious Destination: The Case Of Konya, Turkey - Bilim, Yasin (The international journal of religious tourism and pilgrimage, 2022)
Young tourists represent over 20% of the tourism market and are an important element in current tourism activities. Cultural tourism, encompassing religious tourism, has increased in recent times, however, young tourists exhibit less preference for religious destinations, particularly within their own religions, compared to other options. Their preferences generally lean towards non-spiritual or secular motivations rather than religious based travel motivations. Within this context, this study aims to determine religious tourism motivations, perceptions and related behaviours of young tourists by evaluating their preferences and consumption patterns at religious sites. The study is undertaken on the basis of secondary research supported by primary surveys (n: 387) conducted with young Turkish tourists in Konya, an important religious destination in the central part of Turkey. According to the results, religious tourism attitudes and young tourists’ related behaviours have a high value and have an effect on their motivations and perceptions. Their consumption patterns are focused on religious and entertainment purposes and their preferences are generally based on resting and selfactualisation. Based on these findings, evaluations and suggestions about what needs to be oriented towards young tourists and how to draw more young tourists are presented. For religious tourism destination planners, this study offers some basic profiles and outputs to build useful strategies and to attract more active young tourists and provide useful marketing knowledge about young tourists for the purpose of making religious destinations more attractive to them.